PEMEROLEHAN BAHASA ARAB DI ERA ARTIFICIAL INTELLIGENCE: STUDI PUSTAKA TENTANG POTENSI, STRATEGI, DAN TANTANGAN PEMBELAJARAN BERBASIS AI - Muhammad Ridwan; Ahmad Jezy; M. Shofiyyur Rahman Hawary; M. Apip; Aprijon efendi (Universitas Negeri Semarang, 2025)
The development of Artificial Intelligence (AI) technology has opened new opportunities in the field of education, including in the acquisition of foreign languages such as Arabic. However, the integration of AI into Arabic language acquisition, especially for non-native speakers, still requires further exploration. This study aims to examine the potential of AI in supporting Arabic language acquisition, to identify AI-based learning strategies, and to analyze the challenges encountered in its application. This research uses a qualitative method with a library research approach. Data were collected from various sources, including scholarly journals, books, and articles related to Arabic language learning and AI technology. The data were analyzed descriptively and analytically by classifying and synthesizing relevant information. The findings show that AI holds significant potential in enhancing Arabic language acquisition through features such as chatbots, e-learning platforms, interactive quizzes, and conversation simulations. These strategies provide a more flexible, engaging, and personalized learning experience. However, challenges such as limited vocabulary, mistranslations, overdependence on technology, and access limitations still persist. Therefore, the use of AI should be balanced with contextual and critical approaches to ensure that Arabic language acquisition becomes more meaningful and effective.